2018
DOI: 10.1016/j.jasrep.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Examining the British and Irish Early Bronze Age flat axes of the Greenwell Collection at the British Museum

Abstract: This paper presents the results of metalwork wear-analysis carried out on British and Irish Early Bronze Age copper and copper-alloy flat axes from the collection of Rev. Greenwell (1820-1918) held at the British Museum. Greenwell was a prolific and well-known British antiquarian; part of his collection was sold to John Pierpont Morgan who donated the axes to the museum in 1908. This paper focuses on the copper and copper-alloy flat axes from within this collection, which date to c. 2500-1700 cal BC and are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…the surface (Roberts and Ottaway 2003, 120; Horn 2013). Tight patterns of short scratches on the cutting edge, above the longer scratches and scrapes, might have occurred while the blade was sharpened, although they could also indicate splitting (Roberts and Ottaway 2003; Crellin 2018, 868, fig. 4).…”
Section: Metalwork Wear‐analysismentioning
confidence: 99%
“…the surface (Roberts and Ottaway 2003, 120; Horn 2013). Tight patterns of short scratches on the cutting edge, above the longer scratches and scrapes, might have occurred while the blade was sharpened, although they could also indicate splitting (Roberts and Ottaway 2003; Crellin 2018, 868, fig. 4).…”
Section: Metalwork Wear‐analysismentioning
confidence: 99%
“…The analysis was conducted by one of the authors (RH) following the methodology described in Dolfini and Crellin (2016), adapting the analytical protocol laid out in Dolfini (2011) and Crellin (2018). No casts of the prehistoric swords were taken.…”
Section: Metalwork Wear Analysismentioning
confidence: 99%
“…Emerging to prominence during the period 1,500–1,000 BCE, the palstave axe represents the third major typological development in bronze axe morphology during the Bronze Age in Britain and the first axe type to include a stopridge. Previous studies have detailed traces of woodworking on a number of variants of Bronze Age axes: Scottish flat axes (Moyler, 2007); British and Irish flat axes (Crellin, 2017); flanged axes of the North‐Alpine region (Kienlin & Ottaway, 1998); and, socketed axes of Yorkshire and Scotland (Roberts & Ottaway, 2003). In each of the aforementioned studies, a considerable proportion of axes were found to demonstrate evidence of use.…”
Section: Introductionmentioning
confidence: 99%